Tung Tree (Vernicia fordii, Hemsl.) Genome and Transcriptome Sequencing Reveals Co-Ordinate Up-Regulation of Fatty Acid β-Oxidation and Triacylglycerol Biosynthesis Pathways During Eleostearic Acid Accumulation in Seeds. (21st August 2018) - Cui, Peng; Lin, Qiang; Fang, Dongming; Zhang, Lingling; Li, Rongjun; Cheng, Junyong; Gao, Fei; Shockey, Jay; Hu, Songnian; L, Shiyou
Abstract: The tung tree ( Vernicia fordii ) is one of only a few plant species that produces high oil-yielding seeds rich in α-eleostearic acid (α-ESA, 18:3Δ 9 cis, 11 trans, 13 trans ), a conjugated trienoic fatty acid with valuable industrial and medical properties. Previous attempts have been made to engineer tung oil biosynthesis in transgenic oilseed crops, but these efforts have met with limited success. Here we present a high-quality genome assembly and developing seed transcriptomic data set for this species. Whole-genome shotgun sequencing generated 176 Gb of genome sequence data used to create a final assembled sequence 1, 176, 320 kb in size, with a scaffold N50 size of >474 kb, and containing approximately 47, 000 protein-coding genes. Genomic and transcriptomic data revealed full-length candidate genes for most of the known and suspected reactions that are necessary for fatty acid desaturation/conjugation, acyl editing and triacylglycerol biosynthesis. Seed transcriptomic analyses also revealed features unique to tung tree, including unusual transcriptional profiles of fatty acid biosynthetic genes, and co-ordinated (and seemingly paradoxical) simultaneous up-regulation of both fatty acid β-oxidation and triacylglycerol biosynthesis in mid-development seeds. The precise temporal control of the expression patterns for these two pathways may account for α-ESA enrichment in tung seeds, while controlling the levels of potentially toxic by-products. Deeper understanding of these processes may open doors to the design of engineered oilseeds containing high levels of α-ESA.